Midwives and registered nurses' role and scope of practice in acute early pregnancy care services in Australia: a scoping review protocol. - Freeman, Nicole; Bradfield, Zoe; Cheney, Kate; Warland, Jane (2022)
OBJECTIVE: The objective of this review is to review and synthesize what is documented on the role and scope of practice of midwives and registered nurses working in acute early pregnancy care settings in Australia. INTRODUCTION: Women experiencing complications before 20 weeks of pregnancy may need to attend an acute care service, often a hospital emergency department. Both midwives and registered nurses provide care for women with early pregnancy complications, and it is important that their role and scope of practice is documented. This review will explore the literature relating to acute early pregnancy care in Australia to better understand how midwives' and registered nurses' roles and scope are currently described in this setting. INCLUSION CRITERIA: Any literature that explores the role and scope of practice of midwives and registered nurses who care for women who present to acute care services in Australia with early pregnancy complications will be considered for inclusion in the review. METHODS: A 3-step review process will involve a preliminary search of MEDLINE and ProQuest, followed by a more detailed search of a larger selection of databases, using identified keywords and phrases from the initial search. Reference lists of retrieved literature will then be examined for relevant citations. Literature in English will be considered, including relevant gray literature. Search results will be imported into reference and review support software. Data that align with the inclusion criteria will be organized into tabulated and narrative formats for presentation. SYSTEMATIC REVIEW REGISTRATION NUMBER: Open Science Framework osf.io/5bnqz.